Surface grafting of blood compatible zwitterionic poly(ethylene glycol) on diamond-like carbon-coated stent - Lee, Bong Soo; Shin, Hong-Sub; Park, Kwideok; Han, Dong Keun (SPRINGER, 2011)
Blood compatibility is the most important aspect for blood-contacting medical devices including cardiovascular stents. In this study, the surface of nickel-titanium (TiNi) stent was coated with diamond-like carbon (DLC) and then subsequently grafted by using zwitterion (N+ and SO3 (-))-linked poly(ethylene glycol) (PEG). We hypothesize that this coupling of zwitterion and PEG may significantly improve blood compatibility of DLC-coated TiNi stent. The surface modified TiNi stents, including PEG-grafted stent (DLC-PEG) and zwitterionic PEG-grafted one (DLC-PEG-N-S) were the main focus on the tests of surface characteristics and blood compatibility. The zwitterionic PEG derivatives were obtained from a series of chemical reactions at room temperature. The results exhibited that as compared to the DLC-PEG, the hydrophilicity was much better with DLC-PEG-N-S and significantly increased atomic percentage of oxygen and nitrogen proved the entity of zwitterions on the surface of DLC-PEG-N-S. Meanwhile, the adsorption of blood proteins such as, human serum albumin (HSA) and fibrinogen was found considerably down-regulated in DLC-PEG-N-S, due mainly to the protein-repellant effect of PEG and zwitterion. Microscopic observation also revealed that as compared with the other substrates without zwitterion, the degree of platelet adhesion was the lowest with DLC-PEG-N-S. In addition, DLC-PEG-N-S retained an extended blood coagulation time as measured by activated partial thromboplastin time (APTT). The present results suggested that surface grafting of zwitterionic PEG derivatives could substantially enhance the blood compatibility of TiNi-DLC stent. In conclusion, anti-fouling properties of PEG and zwitterions are expected to be very useful in advancing overall stent performance.
Keywords: ELUTING STENTS; NITINOL ALLOY; IMPLANTATION; PROLIFERATION; CARDIOLOGY; ADHESION; GOLD; POLYMERIZATION; IMMOBILIZATION; BIOMATERIALS